2017
DOI: 10.1016/j.watres.2017.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal illness linked to incidents in drinking water distribution networks in Sweden

Abstract: During recent years, knowledge gaps on drinking water-related gastrointestinal illness have been identified, especially for non-epidemic cases. Pathogen contamination of drinking water during distribution has been suggested to contribute to these cases, but the risk factors are not yet fully understood. During 2014-2015, we conducted an epidemiological study in five municipalities in Sweden, to assess whether incidents in the drinking water distribution system influence the risk of gastrointestinal illness. Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The breakage of two pipelines in the coastal settlement just before the onset of cases, along with reports on flooded wells and sewage overflow, mainly around the central square, indicated a strong possibility of water contamination by sewage during the pipeline breakage. Incidents at the drinking-water distribution systems leading to a loss of water pressure and inadequate physical integrity of the distribution system have been shown to result in an increased risk of gastrointestinal illness [16, 17]. This association indicates that the pathogen contamination originates from an external source, as pathogens can be present in soil and water surrounding the drinking-water pipelines or in sewage, especially if sewage and drinking-water pipelines are close to one another [18] or even on the same level in the pipelines trench [17].…”
Section: Discussionmentioning
confidence: 99%
“…The breakage of two pipelines in the coastal settlement just before the onset of cases, along with reports on flooded wells and sewage overflow, mainly around the central square, indicated a strong possibility of water contamination by sewage during the pipeline breakage. Incidents at the drinking-water distribution systems leading to a loss of water pressure and inadequate physical integrity of the distribution system have been shown to result in an increased risk of gastrointestinal illness [16, 17]. This association indicates that the pathogen contamination originates from an external source, as pathogens can be present in soil and water surrounding the drinking-water pipelines or in sewage, especially if sewage and drinking-water pipelines are close to one another [18] or even on the same level in the pipelines trench [17].…”
Section: Discussionmentioning
confidence: 99%
“…Flushing and chlorine disinfection experiments in a pipe-loop system show that (1) sampling of water from the distribution system for microbiological monitoring can be performed 1 h after flushing, (2) small microbial contaminations in the water phase can be effectively flushed out of the system, (3) a contamination with sand was not completely removed from the system and present in the first few meters, (4) flushing with more than the prescribed three volume replacements removes only a limited number of extra microorganisms, (5) after high risk repair works or incidents shock chlorination is advised to ensure the microbiological safety of the drinking water as flushing is not efficient enough, (6) experiments with pipes with a cultured biofilm yield comparable results to pipes with a natural biofilm. For future experiments pipes with a cultured biofilm can be used, instead of pipes with a natural biofilm which have to be extracted from a distribution system by a drinking water company.…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study in Norway among households downstream of a main break or maintenance works were compared to unexposed households and showed that exposed households reported 1.58 times more gastrointestinal illnesses [5]. A cohort study in Sweden showed that households were 2.0 times as likely to report vomiting complaints and 1.9 times as likely to report acute gastrointestinal illness after a pipe break or works on the distribution system [6]. Risk factors were identified and included the presence of sewage pipelines at the same level as drinking water pipelines in the trench.…”
Section: Introductionmentioning
confidence: 99%
“…A recent epidemiological study conducted in Sweden showed an elevated risk of gastrointestinal illness associated with drinking water distribution incidents such as pipe breaks, pipe repairs, and low‐pressure events (Säve‐Söderbergh et al ). This study showed that the duration of low‐pressure events did not significantly affect risk when compared with the proximity of sewage pipes to drinking water pipes.…”
Section: Waterborne Diseasementioning
confidence: 99%